Photothermally responsive theranostic nanocomposites for near‐infrared light triggered drug release and enhanced synergism of photothermo‐chemotherapy for gastric cancer - Taicheng Zhou; Lili Wu; Ning Ma; Fuxin Tang; Jialin Chen; Zhipeng Jiang; Yingru Li; Tao Ma; Na Yang; Zhen Zong (Bioengineering & Translational Medicine, 2023)
Abstract Near‐infrared (NIR) photothermal therapy plays a critical role in the cancer treatment and diagnosis as a promising carcinoma treatment modalities nowadays. However, development of clinical application has been greatly limited due to the inefficient drug release and low tumor accumulation. Herein, we designed a NIR‐light triggered indocyanine green (ICG)‐based PCL core/P(MEO2MA‐b‐HMAM) shell nanocomposites (PPH@ICG) and evaluated their therapeutic effects in vitro and in vivo. The anticancer drug 5‐fluorouracil (5Fu) and the photothermal agent ICG were loaded into a thermo‐sensitive micelle (PPH@5Fu@ICG) by self‐assembly. The nanoparticles formed were characterized using transmission electron microscopy, dynamic light scattering, and fluorescence spectra. The thermo‐sensitive copolymer (PPH@5Fu@ICG) showed a great temperature‐controlled drug release response with lower critical solution temperature. In vitro cellular uptake and TEM imaging proved that PPH@5Fu@ICG nanoparticles can home into the lysosomal compartments under NIR. Moreover, in gastric tumor‐bearing nude mice, PPH@5Fu@ICG + NIR group exhibited excellent improvement in antitumor efficacy based on the NIR‐triggered thermo‐chemotherapy synergy, both in vitro and in vivo. In summary, the proposed strategy of synergistic photo‐hyperthermia chemotherapy effectively reduced the 5Fu dose, toxic or side effect, which could serve as a secure and efficient approach for cancer theranostics.